2023
DOI: 10.2186/jpr.jpr_d_22_00008
|View full text |Cite
|
Sign up to set email alerts
|

Dental diagnosis for inlay restoration using an intraoral optical coherence tomography system: A case report

Abstract: A 32-year-old man (K.S.) presented to the clinic following diagnosis of a mandibular right second molar. In 2009, he was directly treated with amalgam material for caries on the occlusal surface of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As reported in a clinical study for caries diagnosis (Park et al, 2021), OCT, as it exists today, is most feasible for use on the buccal surfaces of anterior teeth, up to the premolars; therefore, its use for the clinical diagnosis of MIH should still be considered limited. However, Schneider et al (2020) introduced a new OCT probe for intraoral use to diagnose interproximal lesions, and this probe was also evaluated more recently by Son et al (2023) who reported good results with permanent second molars. Currently, there is a trend to combine multiple technologies in a single device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in a clinical study for caries diagnosis (Park et al, 2021), OCT, as it exists today, is most feasible for use on the buccal surfaces of anterior teeth, up to the premolars; therefore, its use for the clinical diagnosis of MIH should still be considered limited. However, Schneider et al (2020) introduced a new OCT probe for intraoral use to diagnose interproximal lesions, and this probe was also evaluated more recently by Son et al (2023) who reported good results with permanent second molars. Currently, there is a trend to combine multiple technologies in a single device.…”
Section: Discussionmentioning
confidence: 99%
“…However,Schneider et al (2020) introduced a new OCT probe for intraoral use to diagnose interproximal lesions, and this probe was also evaluated more recently bySon et al (2023) who reported good results with permanent second molars. Currently, there is a trend to combine multiple technologies in a single device.…”
mentioning
confidence: 99%
“…In vitro studies are useful to simulate circumstances of in vivo studies, but do not fully represent the conditions that distinguish the oral environment. In literature, few studies on partial crown are available for in vivo evaluation [26,29]. Among these methods, 2D analysis in vivo is possible using silicone replica technique or epoxy resin replicas, which represent the only non-invasive methods for patients.…”
Section: Discussionmentioning
confidence: 99%
“…After this phase, 22 articles were included in the final review. The reasons for the exclusion of studies during this last analysis were the following: evaluation of internal fit only [23,24], pilot studies [25], case reports [26], reviews [20,27,28], in vivo studies [29], publication before 1 January 2017 [30][31][32][33], quantitative analysis of fit not expressed in micrometers or percentage values of continuous margin [34][35][36], analysis on wax models [37] or restorations produced with conventional methods [38][39][40][41][42][43] Figure 1.…”
Section: Studies Selectionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is non-invasive optical imaging equipment developed based on the Michelson interferometer to visualize tomography information of tissues several millimeters deep below the surface [1]. Thanks to their real-time imaging capabilities and excellent axial and spatial resolution, optical interference tomography devices are used as major examination tools for ophthalmology, dermatology, oncology, and dentistry [2][3][4][5][6][7][8]. In addition to medical and biomedical applications, optical interference tomography devices are widely applied, including industrial and agricultural applications [9][10][11].…”
Section: Introductionmentioning
confidence: 99%